2017
DOI: 10.37358/mp.17.3.4882
|View full text |Cite
|
Sign up to set email alerts
|

A comparative Histologic and Immunohistochemistry Evaluation Between Normal Aponeurotic Tissue, Fibrotic Aponeurotic Scars and Polypropylene Embedded Aponeurotic Scars

Abstract: Synthetic polypropylene materials are increasingly being used in surgery to repair parietal defects in perineal floor curing surgery, in genital prolapse and stress urinary incontinence. The tissue response to contact with these materials varies, and the inflammatory tissue response may be a prognostic marker of success in surgical interventions that involve contact between tissues and polypropylene materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Decision making in any field is not just the end-point of an analytical assessment but also involves intuition, emotions, awareness, and tacit knowledge [ 88 ]. These processes act as modulators during surgery and contribute to the outcome [ 89 , 90 ]. Mind maps and algorithms use heuristic pathways to facilitate correct decision making and can contribute to safer practice.…”
Section: Cognitive Maps and Algorithms For Safer Laparoscopic Cholecy...mentioning
confidence: 99%
“…Decision making in any field is not just the end-point of an analytical assessment but also involves intuition, emotions, awareness, and tacit knowledge [ 88 ]. These processes act as modulators during surgery and contribute to the outcome [ 89 , 90 ]. Mind maps and algorithms use heuristic pathways to facilitate correct decision making and can contribute to safer practice.…”
Section: Cognitive Maps and Algorithms For Safer Laparoscopic Cholecy...mentioning
confidence: 99%
“…Oxidative stress leads to local chronic inflammation, as a response to damages tissue and increased influx of inflammatory cytokines, complement system activation and endothelial dysfunction [30][31][32][33][34]. In hypoxia and inflammation, Ang2 is freed from Weibel-Palade bodies of the endothelial cells and acts by an autocrine manner, by blocking Tie 2 and promoting vascular destabilization and apoptosis of the endothelial cells, disruptions of the basal membrane and pericytes loss [35][36][37][38]. Faricimab is a 126 kDa bispecific antibody which independently binds Ang2 and VEGF [4,35].…”
Section: Safety Of Intravitreal Faricimab (Ivf)mentioning
confidence: 99%
“…shown that there is a large difference in the inflammatory capacity of the alloplastic material used, which is influenced by the density of the mesh (14). The presence of smaller holes than 1 mm in the mesh, produces more pronounced inflammation and fibrosis, while larger holes give less fibrotic reaction, lack of keloid scar and conserved the elasticity of the inguinal region (1,8,(14)(15)(16)(17).…”
Section: Clinical Studies and Animal Experiments Havementioning
confidence: 99%